PELATIHAN BAHASA INGGRIS DALAM PEMASARAN ONLINE GUNA MEMBANGUN JIWA ENTREPRENEURSHIP - Karjono, Johanes Chemacus Setyo; Sudirman, Anselmus; Putro, Die Bhakti Wardoyo; Muskamal, Muskamal; Wardani, Fita Pramudya (MAJU : Indonesian Journal of Community Empowerment, 2024)
The aim of this service activity is to improve the ability to promote products by creating advertisements in English that are easy to understand. Advertising is a way to market goods or services with the aim of making customers familiar with the goods or services. Marketing products in English via websites or blogs is part of this activity. This service is provided through training methods to MSME residents in Cokrogaten, Bimomartani, Ngemplak, Sleman. Thursday, July 13 2023, training was carried out in residents' homes. One of the results of this activity is that the training participants gain a better understanding of entrepreneurship and the appropriate choice of language to use in advertisements made in English for product marketing. Apart from that, this training also improves participants' skills in making advertisements using English.